Brassinosteroids modulate autophagy through phosphorylation of RAPTOR1B by the GSK3-like kinase BIN2 in Arabidopsis. Issue 4 (3rd April 2023) - Liao, Ching-Yi; Pu, Yunting; Nolan, Trevor M.; Montes, Christian; Guo, Hongqing; Walley, Justin W.; Yin, Yanhai; Bassham, Diane C.
ABSTRACT: Macroautophagy/autophagy is a conserved recycling process that maintains cellular homeostasis during environmental stress. Autophagy is negatively regulated by TOR (target of rapamycin), a nutrient-regulated protein kinase that in plants is activated by several phytohormones, leading to increased growth. However, the detailed molecular mechanisms by which TOR integrates autophagy and hormone signaling are poorly understood. Here, we show that TOR modulates brassinosteroid (BR)-regulated plant growth and stress-response pathways. Active TOR was required for full BR-mediated growth in Arabidopsis thaliana . Autophagy was constitutively up-regulated upon blocking BR biosynthesis or signaling, and down-regulated by increasing the activity of the BR pathway. BIN2 (brassinosteroid-insensitive 2) kinase, a GSK3-like kinase functioning as a negative regulator in BR signaling, directly phosphorylated RAPTOR1B (regulatory-associated protein of TOR 1B), a substrate-recruiting subunit in the TOR complex, at a conserved serine residue within a typical BIN2 phosphorylation motif. Mutation of RAPTOR1B serine 916 to alanine, to block phosphorylation by BIN2, repressed autophagy and increased phosphorylation of the TOR substrate ATG13a (autophagy-related protein 13a). By contrast, this mutation had only a limited effect on growth. We present a model in which RAPTOR1B is phosphorylated and inhibited by BIN2 when BRs are absent, activating the autophagy pathway. When BRs signal and inhibit BIN2, RAPTOR1B is thus less inhibited by BIN2 phosphorylation. This leads to increased TOR activity and ATG13a phosphorylation, and decreased autophagy activity. Our studies define a new mechanism by which coordination between BR and TOR signaling pathways helps to maintain the balance between plant growth and stress responses.